2016
DOI: 10.14429/dsj.1.8952
|View full text |Cite
|
Sign up to set email alerts
|

An Unmanned Tracked Vehicle for Snow Research Applications

Abstract: Lightweight robotic vehicles can be designed for over-snow mobility to carry out a variety of snow and glacier related studies like carrying out ground penetrating radar and global positioning system surveys, collecting snow samples, and carrying out sub-surface experiments on terrain that are dangerous for human movement. Sinkage, resistance to snow compaction, loss of traction and ingestion of snow into the driving system are some of the challenges that an unmanned lightweight tracked vehicle faces in snowbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Moreover, it is observed that (15) can be covered by (17). Hence, the only assumption considered here is (17), in the sense that all the system assumptions are covered by the definition of the problem in (18) and (19) and the regularity of the controller (17). However, the inequalities in ( 16) are quite useful to exclude system cases before testing the solvability conditions that will be presented in Section 3.3.…”
Section: Definition Of the Common Design Requirementmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is observed that (15) can be covered by (17). Hence, the only assumption considered here is (17), in the sense that all the system assumptions are covered by the definition of the problem in (18) and (19) and the regularity of the controller (17). However, the inequalities in ( 16) are quite useful to exclude system cases before testing the solvability conditions that will be presented in Section 3.3.…”
Section: Definition Of the Common Design Requirementmentioning
confidence: 99%
“…If ( 21) is satisfied, then the problem is reduced to that of solving only (53) (see Appendix A) under the constraints ( 17) and (19). Thus, using the definitions in (22), the problem is reduced to that of solving the following set of linear equations with respect to the unknowns γ i , φ M,i , and h i (j, s),…”
Section: Proof See Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…Well-known examples are the crawler machines, such as snowmobiles, that have wide and long treads. A snow country rescue robot HimBot [1] is a typical crawler type robot. Blade Walker [2] is another proposal that uses very Manuscript received September 5, 2018.…”
Section: Introductionmentioning
confidence: 99%